Surgical Healthcare Interventions after Female Genital Mutilation/Cutting-A Review of the Evidence - Malin Jordal; Sharareh Akhavan; Anna Wahlberg (IMR Press, 2022)
Background: Female genital mutilation/cutting (FGM/C) is a global public health problem associated with an increased risk of physical, sexual, and mental health consequences. Surgical healthcare intervention may alleviate negative health consequences related to FGM/C. In this review, we aim to offer an overview of documented effects of surgical healthcare interventions after FGM/C, from the perspectives of both healthcare providers (HCPs) performing such interventions and the women receiving them. Methods: We searched four databases (PUBMED/MEDLINE, CINAHL, PsychInfo, Cochrane Library) for peer-reviewed articles published between 2000 and 2021, and retrieved a total of 1978 citations (1203 + 775). After scrutinizing the citations with the inclusion criteria (1) observable outcomes of surgical healthcare interventions after FGM/C, (2) HCPs' perceptions of FGM/C-related surgical healthcare and experiences of providing surgical care for FGM/C-affected women, and (3) FGM/C-affected women's perceptions and experiences of the effects of FGM/C-related surgical healthcare, we selected 38 articles to include in this review. Results: HCPs and FGM/C-affected women differed in their views on surgical interventions. While providers seemed to suggest premarital defibulation regardless of a woman's age and marital status, affected women voiced social and marital concerns related to defibulation, which sometimes overrode the physical consequences. On the other hand, some providers were reluctant to perform intrapartum defibulation due to uncertainty or misinformation about infibulated women's wishes, while women often expected and desired defibulation prenatally. And while gynecologists demonstrated skepticism towards clitoral reconstruction, most women who had undergone the procedure were satisfied, particularly regarding the psychosocial and sexual aspects. Conclusions: Providers and recipients of surgical interventions after FGM/C seem to display contrasting views on surgical intervention after FGM/C, which may have implications for healthcare recommendations as well as satisfaction. This apparent ambiguity between providers' and recipients' perceptions of surgical interventions needs further investigation.